FACTORS OF TUBAL LIGATION USE FOR AGE LESS THAN FORTY IN URBAN AREAS OF PANGKALPINANG, BANGKA BELITUNG PROVINCE, INDONESIA - Antarini Antarini (Jurnal Biometrika dan Kependudukan (Journal of Biometrics and Population), 2022)
Tubal ligation is a long-term contraceptive and relatively non-adverse, but the problem is that fecundity return surgery for couples who want to change plans to add more children cannot be guaranteed and the cost is very expensive. The research aims to analyze the factors that influence tubectomy contraception for acceptors aged less than 40 years in Pangkalpinang City in 2016. The research type was explanatory with a cross-sectional design. The sample was tubectomy contraceptive acceptors of 95 people. Data analysis was performed using a Chi-square test to determine the relationship between variables. The results showed there was no relationship between maternal education (p=0.512), husband's education (p=0.802), maternal job (p=0.522), parity (p=0.533), knowledge (p=0.484), and support from their husband (p=0.622) with tubectomy less than 40 years of age. The reasons for tubectomy that are most often cited are  related to health factors and family factors/number of children. Almost all respondents (98%) stated that they were satisfied after having a tubectomy seen from several factors including the reasons underlying the desire for tubectomy, the amount of support, the attitude, and role of the husband, support from the family, community, and role models, and easy access to costs and places to get tubectomy health services.